Strartegic human resource management: theory and practice - Salaman, Graeme; Storey, John; Billsberry, Jon ed. (London : Sage publications, 2005)
Business
Keywords: Human resource management; Strategic human resource management; Business performance; Relationships; New organizational forms; Missionary management